The Mediating Effect of Public Service Motivation on the Relationship between Organizational Citizenship Behavior and Organizational Commitment among Local Government Employees in Davao Region - De la Salde, Ernie Dango; Gempes, Gloria Pacifico (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The purpose of the study was to determine if the public service motivation has a significant mediating effect on the relationship between organizational citizenship behavior and organizational commitment among the local government employees in selected cities in Davao Region, Philippines. The design used was non-experimental quantitative research utilizing correlation technique. Descriptive statistics, Pearson r, Regression Analysis, Mediation through Sobel test and Medgraph were the tools employed to attain the objectives of the study. The 600 respondents were found to show high levels of organizational citizenship behavior and organizational commitment, while the overall level of public service motivation was very high. It was found out that the three variables were significantly correlated. However, the result failed to prove the mediating effect of public service motivation on the relationship between organizational citizenship behavior of government employees and their organizational commitment. The result, signify that the significant influence of organizational citizenship behavior on organizational commitment was not affected by public service motivation.